Chloroplast‐targeted Hsp90 plays essential roles in plastid development and embryogenesis in Arabidopsis possibly linking with VIPP1. Issue 2 (13th August 2013) - Feng, Juanjuan; Fan, Pengxiang; Jiang, Ping; Lv, Sulian; Chen, Xianyang; Li, Yinxin
Abstract The Arabidopsis genome contains seven members of Hsp90. Mutations in plastid AtHsp90.5 were reported to cause defects in chloroplast development and embryogenesis. However, the exact function of plastid AtHsp90.5 has not yet been defined. In this study, albino seedlings were found among AtHsp90.5 transformed Arabidopsis, which were revealed to be AtHsp90.5 co‐suppressed plants. The accumulation of photosynthetic super‐complexes in the albinos was decreased, and expression of genes involved in photosynthesis was significantly down‐regulated. AtHsp90.5 T‐DNA insertion mutants were embryo‐lethal with embryo arrested at the heart stage. Further investigation showed AtHsp90.5 expression was up‐regulated in the siliques at 4 days post anthesis (DPA). Confocal microscopy proved AtHsp90.5 was located in the chloroplasts. Plastid development in the AtHsp90.5 mutants and co‐suppressed plants was seriously impaired, and few thylakoid membranes were observed, indicating the involvement of AtHsp90.5 in chloroplast biogenesis. AtHsp90.5 was found to interact with vesicle‐inducing protein in plastids 1 (VIPP1) by bimolecular fluorescence complementation system. The ratio between VIPP1 oligomers and monomers in AtHsp90.5 co‐suppressed plants drastically shifted toward the oligomeric state. Our study confirmed that AtHsp90.5 is vital for chloroplast biogenesis and embryogenesis. Further evidence also suggested that AtHsp90.5 may help in the disassembly of VIPP1 for thylakoid membrane formation and/or maintenance.